2018
DOI: 10.1051/swsc/2018043
|View full text |Cite
|
Sign up to set email alerts
|

Shock deceleration in interplanetary coronal mass ejections (ICMEs) beyond Mercury’s orbit until one AU

Abstract: The CDPP propagation tool is used to propagate interplanetary coronal mass ejections (ICMEs) observed at Mercury by MESSENGER to various targets in the inner solar system (VEX, ACE, STEREO-A and B). The deceleration of ICME shock fronts between the orbit of Mercury and 1 AU is studied on the basis of a large dataset. We focus on the interplanetary medium far from the solor corona, to avoid the region where ICME propagation modifications in velocity and direction are the most drastic. Starting with a catalog of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…As expected, the transit velocities are lower than the initial velocities observed by LASCO, but larger than the velocities measured at 1 au by ACE. Deceleration in the interplanetary medium is expected for fast ICMEs (Gopalswamy et al 2001a), as confirmed with several cases of ICMEs observed at different distances between the solar corona and 1 au (Grison et al 2018). The aforementioned velocities also suggest that CME2 experienced a higher deceleration than CME1 during its travel between the Sun and the Earth.…”
Section: The Cme-cme Interactionsupporting
confidence: 70%
“…As expected, the transit velocities are lower than the initial velocities observed by LASCO, but larger than the velocities measured at 1 au by ACE. Deceleration in the interplanetary medium is expected for fast ICMEs (Gopalswamy et al 2001a), as confirmed with several cases of ICMEs observed at different distances between the solar corona and 1 au (Grison et al 2018). The aforementioned velocities also suggest that CME2 experienced a higher deceleration than CME1 during its travel between the Sun and the Earth.…”
Section: The Cme-cme Interactionsupporting
confidence: 70%
“…We now test the association between the discontinuities and the halo CMEs based on velocity comparisons. As fast ICME shocks are progressively slowing down in the interplanetary medium at least up to 1 AU (Gopalswamy et al, 2000;Grison et al, 2018), we expect v bal to be lower than the CME velocity v estimated from coronagraph observations and to be larger than the velocity observed at L1 (v L1 ). This is the case for the discontinuity observed the 25 July 13:00 UT (flare-related CME #6) (v L1 = 520; v bal = 625; v = 2285 km·s −1 ).…”
Section: Annexmentioning
confidence: 80%
“…In addition, the ICMEs could simply have decelerated, e.g. Grison et al (2018), to the ambient slow v sw of ∼250 kms −1 . The possible merging of the two ICMEs would have resulted in a complex ICME-solar wind outflow at the comet, which may have compressed the fast solar wind ahead.…”
Section: Accepted Articlementioning
confidence: 99%
“…It is far more likely that this turbulent period is associated with an ICME-on-ICME interaction from the last two ICMEs reported in Table 3 and Figure 28. In addition, the ICMEs could simply have decelerated, for example, Grison et al (2018), to the ambient slow v sw of ∼250 km s −1 . The possible merging of the two ICMEs would have resulted in a complex ICME-SW outflow at the comet, which may have compressed the fast SW ahead.…”
Section: Cr 2134mentioning
confidence: 99%